Dexamethasone Increases Cdc42 Expression in Human TM-1 Cells. (March 2015) - Qiu, Xuan; Wu, Kaili; Lin, Xianchai; Liu, Qian; Ye, Yiming; Yu, Minbin
Abstract Purpose: Changes in the cytoskeletal organization of the human trabecular meshwork (HTM) is thought to be responsible for primary open-angle glaucoma (POAG) pathologies. Cdc42 is a Rho GTPase; Rho GTPases are important modulatory agents of the cytoskeleton. This study aimed to investigate the effects of dexamethasone (DEX) on Cdc42 in a transformed HTM cell line, TM-1 to understand the molecular pathologies underlying POAG. Methods: TM-1 cells were cultured in vitro. The cultures were treated with DEX at 10−6 and 10−7 M for 1–4 days. Cdc42 was silenced using small interfering RNA (siRNA). The expression levels of Cdc42 in the TM-1 cells were measured using reverse transcription (RT)–PCR, western blotting analysis and immunofluorescence. Its downstream effectors, p21-activated kinase phosphorylation (phospho-PAK) and myosin light chain kinase (MLCK), were measured using western blotting analysis. In addition, the F-actin of TM-1 cells was stained using phalloidin. Results: The mRNA and protein levels of Cdc42 showed an increase in TM-1 cells with DEX treatment and a decrease in TM-1 cells transfected with Cdc42 siRNA. Moreover, phospho-PAK levels increased, whereas MLCK levels appeared to decrease, with DEX treatment. The F-actin of DEX-treated TM-1 cells displayed a rearrangement. Cdc42 siRNA decreased the expression of Cdc42 and its related proteins, resulting in an attenuation of the effects of DEX on Cdc42 and F-actin organization in TM-1 cells. Conclusions: DEX increases Cdc42 expression in TM-1. This may represent a potential mechanism of DEX-induced HTM cytoskeletal rearrangement.